2015
DOI: 10.1016/j.physa.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting missing links via correlation between nodes

Abstract: As a fundamental problem in many different fields, link prediction aims to estimate the likelihood of an existing link between two nodes based on the observed information. Since this problem is related to many applications ranging from uncovering missing data to predicting the evolution of networks, link prediction has been intensively investigated recently and many methods have been proposed so far. The essential challenge of link prediction is to estimate the similarity between nodes. Most of the existing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 44 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…degree, clustering), the hybrid-based methods have been studied. Liao et al 28 presented a novel correlation-based index and combined it with the AA index to achieve better performance. Zeng 29 presented a hybrid index through combining the CN index with the preferential attachment index (PA).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…degree, clustering), the hybrid-based methods have been studied. Liao et al 28 presented a novel correlation-based index and combined it with the AA index to achieve better performance. Zeng 29 presented a hybrid index through combining the CN index with the preferential attachment index (PA).…”
Section: Related Workmentioning
confidence: 99%
“…In Ref. 28, the feature of one node i was characterized as an attribute vector v i derived from the adjacency matrix A of network graph, where v i ¼ ða i1 ; a i2 ; . .…”
Section: Relevance Between Layers In Multiplex Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…All non-observed links are ranked according to their similarities, and the non-observed links connecting nodes that are more similar are supposed to have higher existence likelihoods. Node similarity can be defined by using the essential attributes of nodes: two nodes are considered similar if they have many common features or correlated topological structures [1,15,26]. Many studies found that there are substantial levels of topical similarity among individuals who are close to one another in the social network.…”
Section: Related Workmentioning
confidence: 99%
“…An alternative classification distinguishes between algorithms employing purely structural information (either binary or weighted [8]) and algorithms making use of some kind of external information as well (e.g. nodes attributes [22]).…”
Section: Introductionmentioning
confidence: 99%